Severe enteropathy with villous atrophy in prolonged mefenamic acid users – a currently under-recognized in previously well-recognized complication: Case report and review of literature. Issue 44 (November 2017) - Kaosombatwattana, Uayporn; Limsrivilai, Julajak; Pongpaibul, Ananya; Maneerattanaporn, Monthira; Charatcharoenwitthaya, Phunchai
Abstract: Rationale: Mefenamic acid-induced enteropathy may be an under-recognized condition because few reported cases and no review of literature to comprehensively describe all reported cases exist. From inception until February 2017, a systematic literature search identified twenty original reports of cases of mefenamic acid-induced enteropathy. Additional five cases were identified at our hospital. All cases were included in the analyses. Patient concerns: Most patients had been regularly taking therapeutic dosages of mefenamic acid for at least three months before symptoms developed. All patients presented with chronic diarrhea with significant weight loss. Approximately one-third of the cases had some degree of anemia and hypoalbuminemia. Diagnoses: Endoscopic findings could range from very mild abnormalities, such as mild atrophic mucosa, to marked abnormalities, such as blunted villi with scalloping appearance in the small intestine and inflamed mucosa with a few superficial ulcers in the ileum and colon. Pathological findings included flattened small intestinal villi and mixed inflammatory infiltrates including eosinophils in lamina propria. Intervention: After identifying history of prolong mefenamic acid exposure, all patients were prescribed to stop this medication. Nutritional support and substitutional treatment for mefenamic acid were provided as well. Outcomes: All symptoms responded dramatically to drug withdrawal. Some patients could change to use other nonsteroidal anti-inflammatory drugs (NSAIDs) without symptoms reoccurring. Lessons: Unlike other traditional NSAIDs, mefenamic acid could induce intestinal villous atrophy. An adequate drug history is crucial to identifying the condition. Protracted diarrhea occurring during treatment should be the indication to cease the medicine promptly. Abstract : Supplemental Digital Content is available in the text